HUKUM PRIVAT ISLAM TERHADAP PERNIKAHAN DINI PERSPEKTIF SOSIAL BUDAYA - S, Samsidar; Misbahuddin, Misbahuddin; Kurniati, Kurniati (Jurnal AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2024)
Child marriage is a complex and multidimensional social issue occurring in various parts of the world, including Indonesia. This phenomenon is influenced by diverse cultural norms, social pressures, and economic conditions. The practice of early marriage is often regarded as a deep-rooted tradition, where marrying off young girls is seen as a way to protect family honor and reduce economic burden. Although there are laws regarding the minimum age for marriage, their implementation is often inconsistent, and cultural norms frequently dominate. This research employs a qualitative approach to analyze early marriage from cultural, social, and Islamic private law perspectives. Data were collected through literature studies, including books and journals, to produce a comprehensive understanding of this issue. The analysis results indicate that early marriage negatively affects the quality of education and life for adolescents, their health, and contributes to the cycle of poverty. Therefore, this research advocates for a holistic approach involving all stakeholders to protect children's rights and reduce the practice of early marriage in society.